2012
DOI: 10.1371/journal.pone.0030556
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Multimorbidity in the Aged Population. Results from the KORA-Age Study

Abstract: Multimorbidity is a common problem in aged populations with a wide range of individual and societal consequences. The objective of the study was to explore patterns of comorbidity and multimorbidity in an elderly population using different analytical approaches. Data were gathered from the population-based KORA-Age project, which included 4,127 persons aged 65–94 years living in the city of Augsburg and its two surrounding counties in Southern Germany. Information on the presence of 13 chronic conditions was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
187
3
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(226 citation statements)
references
References 39 publications
(63 reference statements)
26
187
3
10
Order By: Relevance
“…This burden of disease is significantly higher compared to the 58.6% of a large elderly German population (aged 65-94 years) who had not been suffering from AKI. 32 van Oostrom et al 33 demonstrated that certain comorbid conditions occurred in clusters (eg, cardio/metabolic cluster), and thus specific subgroups of patients within these clusters will, independent from age, have rates of multimorbidity up to 70%, similar to our findings. For example, patients with Acute Kidney Injury Network (AKIN) II-III after coronary angiography have an increased risk of hospital readmission, with a significant hazard ratio (HR) of 3.6 for myocardial infarction and an even higher HR for heart failure (HR: 11.9).…”
Section: Morbiditysupporting
confidence: 88%
“…This burden of disease is significantly higher compared to the 58.6% of a large elderly German population (aged 65-94 years) who had not been suffering from AKI. 32 van Oostrom et al 33 demonstrated that certain comorbid conditions occurred in clusters (eg, cardio/metabolic cluster), and thus specific subgroups of patients within these clusters will, independent from age, have rates of multimorbidity up to 70%, similar to our findings. For example, patients with Acute Kidney Injury Network (AKIN) II-III after coronary angiography have an increased risk of hospital readmission, with a significant hazard ratio (HR) of 3.6 for myocardial infarction and an even higher HR for heart failure (HR: 11.9).…”
Section: Morbiditysupporting
confidence: 88%
“…174 In a population aged ≥ 75 years, 60% reported one and 33.4% reported two or more health problems. 175 Among patients with advanced symptoms of osteoarthritis recruited into the APEX study, comorbid conditions were common; in patients receiving total hip and knee replacement, 64% and 71% of patients, respectively, reported at least one condition additional to osteoarthritis.…”
Section: Resultsmentioning
confidence: 99%
“…67.3% in German population, 58.6% in Southern Germany population, 55% in the Swedish population. 4,18,22,23 It should, however be noted that the differences observed in multimorbidity between Indonesia and other countries may not comparable due to sociodemographic differences.…”
Section: Discussionmentioning
confidence: 99%